Content of Children's Loss of Control Eating Episodes Assessed by Self‐Report and Laboratory Test Meal. (10th September 2013) - Theim, Kelly R.; Wilfley, Denise E.; Beach, Elizabeth; Tanofsky‐Kraff, Marian; Goldschmidt, Andrea B.
Abstract Pediatric loss of control (LOC) eating heightens risk for excessive weight gain and further disordered eating. Assessment of LOC typically involves self‐report interview or laboratory test meal, although no study has concurrently examined data from both methods. We gathered eating episode data via interview (Child Eating Disorder Examination; ChEDE) and a laboratory test meal, among 22 overweight girls (aged 7–12 years) reporting LOC eating. Children consumed more energy during ChEDE episodes, although ChEDE and test meal episodes did not differ in macronutrient content. Episodes' correlation for amount consumed (grams) did not reach significance, p = .076. In exploratory analyses among the seven children reporting LOC during the test meal, episodes were significantly correlated for grams consumed. Findings provide preliminary data to suggest that semi‐structured interviews accurately capture children's LOC episode quantity. Episodes did not qualitatively differ, although children reported consuming more energy during self‐reported episodes. Replication is warranted in larger studies. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.